Die kerkregtelike ontwikkeling van godsdiensvryheid in die NG Kerk tussen 1962 en 2007 - Heine, QE; Coertzen, P (Nederduitse Gereformeerde Teologiese Tydskrif, 2009)
The development of religious freedom in the canonical law in the Dutch Reformed Church between 1962 and 2007 From as far as 1652 the Christian religion was a privileged religion in South Africa. The privileged situation of the Dutch Reformed Church in its relation to the state made it unnecessary for them to discuss or define the concept of freedom of religion. Consequently the church gave silent consent to the state’s limited application of religious freedom. In and outside the church there was an ongoing debate that helped the church to formulate its role in religious freedom, which resulted in the document “Church and Society” (1986–1990). With the new Constitution of South Africa in 1996, a new situation developed for the Dutch Reformed Church as well as other churches. The church realized that it must define and take up its own legal position on religious freedom, which is guaranteed in the Constitution of South Africa.